The lived experiences with paediatric hearing loss: medical doctors as parents of deaf children - Birdsey, Bianca Caren (My University, 2020)
Paediatric hearing loss is an important aspect of neurodevelopment. Optimal management includes a holistic family-centered approach. In spite of knowing this, the field of paediatric hearing loss is largely influenced by a medical model view of disability. Exposure to the lived experience may be the catalyst for the necessary shift towards holistic family care. This study explored the lived experiences of South African medical doctors who are also parents of deaf children. The aim being to better understand the field of paediatric hearing loss through their insights gained as parents. Interpretative Phenomenological Analysis was the approach used for this qualitative enquiry. Five participants were selected using purposive sampling and an indepth semi-structured interview used as the data instrument. Thereafter, three levels of thematic analysis were conducted. Four organizing themes emerged reflecting the complex journey of parenting deaf children, insights into the interactions and support received, as well as the reflections on the inadequate knowledge of doctors about paediatric deafness. Participants acknowledged the power of the lived experience in changing their own practice as both parents and practitioners.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree, MSc Med Child Health (Neurodevelopment)